Narrative construction of self in dreamwork experiences - Tan-Mansukhani, Roseann R. (Philippine Journal of Psychology, 2004)
This study looked into the application of narrative in the study of the self. Specifically it described the self-construction of dreamers in the narratives of their dreamwork experience, the temporal movement and the reflexivity of the constructed self, and the impact of their dreamwork experience. Twelve female college students were interviewed to obtain a total of 24 dreamwork narratives. Narrative analysis was used to analyze the structure and content of the dreamwork narratives. Results reveal that the dreamers' constructed self is relational and self-valuing, has the reflexive capacity for self-assessment and insights. The progressive narrative was predominant in showing the goal-based temporal movement of the self, and change occurred in the waking lives of the dreamers as an effect of the dreamwork experience.